Periorbital Hyperpigmentation: Overcoming the Challenges in the Management - Agrawal, Sudha (Nepal Journal of Dermatology, Venereology & Leprology, 2018)
Periorbital hyperpigmentation, also referring as dark circles or periorbital melanosis, is not a medical problem but can be a significant cosmetic concern for a large number of individuals and they try to find a treatment for this condition. This condition affects individuals in a wide range of ages, both sexes and all races. The therapeutic approach must vary with cause as it is multifactorial. Possible causes include excessive pigmentation, volume loss, skin laxity, tear trough, increased prominence and density of subcutaneous vasculature and orbital structural problem. Treatment modalities include topical bleaching agents, chemical peeling, and lasers, injectable fillers, fat transfer, high intensity focused ultrasound and surgery as monotherapy or in combination therapy to target the contributing factors of periorbital hyperpigmentation.